Redesign brandingu hororového filmů - Demchenko, Anna; Dědic, Filip; Rešovská, Barbora; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This bachelor thesis focuses on creating a modern branding for the horror film Suspiria (1977) that ensures genre recognizability while being visually appealing to contemporary audiences. The theoretical part analyses a curated selection of horror movie posters from different decades to identify recurring visual elements that regularly appear in horror posters and help viewers recognise the genre. These insights form the basis for understanding which visual cues support genre recognition and can be effectively incorporated into a contemporary redesign. The thesis also discusses the role of film branding and posters as essential carriers of visual identity. The practical part develops a new branding concept for Suspiria, consisting of a poster, a Blu-ray collector’s edition, and a vinyl record design. The design process draws on visual research, mood boards, and exploration of multiple conceptual directions before establishing a final cohesive visual identity. To evaluate whether the new branding achieves genre recognizability and visual appeal, an online survey was conducted. The results indicate that the redesigned materials communicate the atmosphere and genre features of horror well and are also perceived as visually appealing by contemporary viewers. Overall, the thesis demonstrates a coherent branding solution for Suspiria that functions effectively across the poster, Blu-ray edition, and vinyl release.
Vedoucí práce: Filip Dědic
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: multimédia v ekonomické praxi [obor bakal. práce]; bakalářské práce; bachelor's theses